2007
DOI: 10.1016/j.ejheart.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Promoter polymorphism of the matrix metalloproteinase 3 gene is associated with regurgitation and left ventricular remodelling in mitral valve prolapse patients

Abstract: Background and aims: Mitral valve prolapse (MVP) is common and highly variable in its severity, but the factors underlying this variability are unclear. In this study, we tested the hypothesis that polymorphic variations in Matrix Metalloproteinase (MMP) genes might be predictors of left ventricular (LV) remodelling and severity of regurgitation in MVP. Methods and results: 70 MVP patients and 75 normal subjects were studied. We performed comprehensive echocardiography and analyzed promoter polymorphisms in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…HDL cholesterol was measured as cholesterol after precipitation of apolipoprotein Bcontaining lipoproteins with phosphotungstic-Mg++ (Boehringer Mannheim, Mannheim, Germany). Polymerase chain reaction was performed using primer sequences derived from published data [24].…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…HDL cholesterol was measured as cholesterol after precipitation of apolipoprotein Bcontaining lipoproteins with phosphotungstic-Mg++ (Boehringer Mannheim, Mannheim, Germany). Polymerase chain reaction was performed using primer sequences derived from published data [24].…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…48 It is interesting that in another study of MVP patients, an MMP-3 promoter haplotype-1612 5A/5A polymorphism was associated with severe mitral regurgitation and more pronounced left ventricular remodeling. 49 It is speculated that the MMP-3 promoter 5A/5A polymorphism may result in increased MMP-3 expression in the myocardium, which then accentuates the adaptive response of the myocardium to the volume overload of mitral regurgitation and hence more adverse disease course. 49 This suggests that genetic variation influences the disease course in MVP.…”
mentioning
confidence: 99%
“…49 It is speculated that the MMP-3 promoter 5A/5A polymorphism may result in increased MMP-3 expression in the myocardium, which then accentuates the adaptive response of the myocardium to the volume overload of mitral regurgitation and hence more adverse disease course. 49 This suggests that genetic variation influences the disease course in MVP.…”
mentioning
confidence: 99%
“…Our interest is supported by experimental studies on animal models and humans, which have suggested a key role of MMPs in their onset and progression [7][8][9][10][11][12][13][14][15]. However, in literature, there are few data [16,17] showing associations of SNPs in MMP genes with MVD susceptibility. Thus, our study represents the first report that analyzed, in a perspective manner, associations of functional genetic variants in the MMP-2 and MMP-9 genes not only with MVD risk but also with its severity and complications, as well as with long-term outcome after surgical approaches (i.e., mitral valve replacement or plastic surgery).…”
Section: Discussionmentioning
confidence: 72%
“…Increased systemic and tissue levels of MMPs in cases affected by degenerative sporadic MVDs and with stenosis or regurgitation complications have been also assessed [7][8][9][10][11][12][13][14][15]. In contrast, no exhaustive data about eventual associations between single nucleotide polymorphisms (SNPs) in MMP genes and the risk of degenerative sporadic MVDs are reported until now in literature, since they are a very limited number [16,17]. However, genetic association studies have the potential to identify molecular pathways as early diagnostic biomarkers and targets.…”
Section: Introductionmentioning
confidence: 99%